‘CAG has been good for me as a farmer—it has made it much easier to stay on ART’. Patient and healthcare worker experiences with ART community adherence groups in two Zambian communities - Lazarus Jere; Chiti Bwalya; Joseph M. Zulu; Wilbroad Mutale (Cogent Public Health)
Background The UNAIDS 90-90-90 targets, aimed at ending the AIDS pandemic by 2030, have increased ART initiation among people living with HIV (PLWH). However, retention in care remains a challenge in some settings due to the growing patient load on already overwhelmed health systems. Decentralizing HIV services to the community is critical to decongest facilities and improve access. This study explored the experiences of patients and healthcare workers (HCWs) with retention in care under Zambia’s Community Adherence Group (CAG) model.Method This qualitative study was nested within a community ART retention project that implemented three decentralized ART models across five communities in Zambia. Between September and December 2018, data were collected through audio-recorded focus group discussions (FGDs) with purposively selected PLWH (8 FGDs, n = 42) enrolled in the CAG model and interviews with healthcare providers (n = 6). Recordings were transcribed verbatim, translated into English, and analyzed thematically using the Social Ecological Model to explore participants’ experiences.Results Patient retention in CAGs was influenced by factors across different levels of the Social Ecological Model. At the individual level, participants noted increased free time and reduced opportunity costs, enabling them to access ART while continuing with livelihood activities. Interpersonal factors, such as peer support and shared knowledge during group meetings, further enhanced engagement. At the organizational level, reduced clinic-based stigma encouraged continued care. Although the CAG helped with patient retention in care, a few participants felt it didn’t address conflicts with patients’ livelihood activities, particularly business ventures, which required patients to travel outside the community for an extended period.Conclusions CAG models were perceived as practical models for improving ART patient retention because they provided an important option for PLWH to access ART services as close as possible to their homes. For the models to be effective, it is important to consider the socio-economic context, including various livelihood situations for PLWH.